Emile Durkheim and the Sociological Theory of Action (Andamios, Revista de Investigación Social, 2014)
The problem of human action in the Durkheimian sociological theory has often been ignored. This article intends to address this problem. To do this, I first introduce a simple but radical analysis of the main concepts of Durkheim’s sociology —social fact, collective representations, morality— to find there some elements of a theory of social action, then try to reconstruct how the author uses some categories within the semantics of action (motive, means, purpose, effort, desire, intention), and finally present selected concrete analysis that are rarely considered as elements of a theoretical discourse, but may serve as a reference to enrich the general outlines of the theory of action.
Keywords: Durkheim; action; sociological theory; norms; representations